Design and Impedance Modeling of Complementary Circular Loop FSS at 2.4 GHz - Abd Aziz, Mohamad Zoinol Abidin; Abu Hussin, Farhana; Ahmad, Badrul Hisham; Suaidi, Mohamad Kadim; Md Fauzi, Noor Azamiah (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper presents the design of a circular loop for Frequency Selective Surfaces (FSS) based on complementary techniques for 2.4GHz application. The design of circular loop FSS is simulated using CST Microwave Studio software. The simulation process is based on the characteristics of the reflection coefficient (S11) and transmission coefficient (S21) of the FSS. In this paper, there are two designs that have been presented, namely Design A, which is double circle loop in horizontal axes and Design B is double circle loop in horizontal axes using complementary techniques. It was found that the best performance of the FSS is Design B in terms of return loss and bandwidth. The return loss for Design B is -29.13dB and the bandwidth is 0.39211 GHz at a frequency range from 2.2012 GHz to 2.5933 GHz.